PERBEDAAN BERKUMUR LARUTAN EKSTRAK SIWAK (Salvadora persica) TERHADAP SEKRESI SALIVA RONGGA MULUT LANJUT USIA DENGAN HIPERTENSI (HT), DIABETES MELITUS (DM) DAN TIDAK MEMILIKI PENYAKIT SISTEMIK DI PANTI SOSIAL TRESNA WERDHA GAU MABAJI GOWA TAHUN 2017 - Syamsiah Syam; Risnayanti Anas; Andi Nelva Yunita (Fakultas Farmasi UMI, 2018)
Background of Study: Saliva is a complex oral fluid that has an important role associated with biological processes in the oral cavity. Age changes are known to have an effect on decreasing saliva production. Likewise with systemic diseases such as hypertension and diabetes mellitus. Chemical prevention of acid imbalance in the saliva is conducted by rinsing using a siwak extract solution. Chemical content in siwak extract can increase the secretion in the saliva in the oral cavity because it has a bactericidal effect that will prevent acid production from oral bacteria. Objective of Study: To determine the difference of rinsing by using siwal extract solution on salivary secretion of the oral cavity of elderly people who have hypertension, diabetes mellitus, and do not have systemic diseases. Method: This study is pre-experiment with one group pretest and post-test design. The sample of the study was elderly people in a social housing. Also, the research used paired t-test. Result: This study shows the average change in hypertension 1.185 mL/5minute with probability value 0.000, diabates mellitus 1,358mL/5minute with probability value 0.000, does not have systemic disease 1.057 mL/5minute with probability value 0,000 <0,05 meaning there is difference. Conclusion: The difference of mouth washing of 25% extract of siwak solution to elderly salivary secretion in hypertension, diabetes mellitus and did not have systemic disease in social house of tresna werdha gau mabaji gowa.